Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kompetensi Guru di Madrasah Ibtidaiyah Sumber Bunga Seletreng Kapongan Situbondo - Zaini Zaini; Ashari Ashari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Academic supervision is a series of activities to help teachers develop their ability to manage the learning process in achieving learning goals. In preparing the academic supervision plan that must be considered is the preparation of the schedule, objectives, approaches, techniques and instruments needed.The research method used is qualitative research with descriptive, theoretical and empirical approaches. Data collection techniques using observation, interviews and documentation. As for analyzing the data using reduction and verification. Meanwhile, in testing the validity of the data using source and time triangulation.The results showed that the most frequently used approach was the collaborative approach and the techniques used were group supervision techniques (teacher meetings, workshops and MGMP) and individual techniques (class visits and class observations). Implementation of good academic supervision can improve the professional competence of teachers so as to produce quality graduates. Factors that support management of the academic supervision of madrasah heads in improving teacher competence are teacher education, teacher teaching experience, training experience that has been carried out by teachers, motivation, infrastructure, and supervision of school principals. The inhibiting factors were lack of teaching experience, lack of training, lack of self-motivation, lack of academic supervision from the head of the madrasah, and educational level qualifications.